Strategy for Actualization of the Entrepreneurship-Based Curriculum: A Case Study at Madrasah Aliyah - Zaini, Mohammad (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
This article comprehensively examines the strategy employed for the modernization and actualization of an entrepreneurship-based curriculum at Madrasah Aliyah Miftahul Ulum in Lumajang. The study adopts a qualitative research approach, utilizing a descriptive method through a case study framework and an analysis of relevant entrepreneurship curriculum documents with seven sources of information, including the principal, vice principal, teachers, and 3 students. The research data, gathered from interviews, observations, and documentation, undergoes rigorous analysis through data condensation, data display, and conclusion formulation. The findings indicate that the strategy for the modernization and actualization of the entrepreneurship-based curriculum at MA Miftahul Ulum encompasses several key components, including the formulation of the vision, mission, and objectives of the curriculum; an analysis of individual expertise and responsibilities and an evaluation of program implementation by the entrepreneurship education implementation team.